2013
DOI: 10.1002/jbmr.1958
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 promotes bone angiogenesis by increasing vegf expression and release in the bone environment

Abstract: Activating transcription factor 4 (ATF4) is a critical transcription factor for bone remodeling; however, its role in bone angiogenesis has not been established. Here we show that ablation of the Atf4 gene expression in mice severely impaired skeletal vasculature and reduced microvascular density of the bone associated with dramatically decreased expression of hypoxia inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) in osteoblasts located on bone surfaces. Results from in vivo studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 64 publications
3
54
0
Order By: Relevance
“…22 The ATF4 expression level was significantly increased (p<0.05) in the joint synovium during OA progression at (4 and 8 weeks post-DMM) in PKCδ null mice ( figure 5E, F). Moreover, we found that introduction of siRNA for PKCδ into either human endothelial or synovial cells stimulated the expression of both ATF4 and VEGF (figure 5G-J).…”
Section: Loss Of Pkcδ Augments Knee Joint Angiogenesismentioning
confidence: 92%
“…22 The ATF4 expression level was significantly increased (p<0.05) in the joint synovium during OA progression at (4 and 8 weeks post-DMM) in PKCδ null mice ( figure 5E, F). Moreover, we found that introduction of siRNA for PKCδ into either human endothelial or synovial cells stimulated the expression of both ATF4 and VEGF (figure 5G-J).…”
Section: Loss Of Pkcδ Augments Knee Joint Angiogenesismentioning
confidence: 92%
“…TRAP-positive multinucleated cells (MNCs) per well were counted using light microscopy. The TRAP staining technique for bone sections was previously described (Zhu et al, 2013). The osteoclast surface/bone surface (Oc.S/BS) and osteoclast numbers/bone perimeter (Oc.N/BPm) in both primary and secondary spongiosa of tibiae were measured using Image Pro Plus 7.0 software.…”
Section: In Vitro and In Vivo Osteoclast Formationmentioning
confidence: 99%
“…The PHD-HIF-α pathway is also involved in bone repair, angiogenesis, and osteogenesis (Wang et al, 2007;Wan et al, 2008;Zhu et al, 2013). Thoms et al identified PHD2 as the primary enzyme regulating HIF-2α stability in human chondrocytes.…”
Section: Introductionmentioning
confidence: 96%
“…These changes are carefully controlled by a large number of hypoxia-inducible genes [2]. Among these genes, hypoxia-inducible factor 1a (HIF1a) is the key transcription factor induced by hypoxia, increasing the expression of many genes that are involved in metastasis, tumor recurrence, and angiogenesis [3][4][5]. Hypoxia also promotes tumor cell resistance to apoptosis [6]; however, the detailed mechanism is not fully understood.microRNAs are small, non-coding, single-stranded RNAs that are 20-23 nucleotides in length and that suppress gene expression in a sequencespecific manner [7].…”
Section: Introductionmentioning
confidence: 99%